A Case Study of Forecasted Earnings Acceleration and Stock Selection in Global and Emerging Stock Markets - Guerard, John; Saxena, Anureet (Frontiers in Applied Mathematics and Statistics, 2018)
The allocation of scarce economic resources so as to maximize societal good is at the very core of human economic development. The key contribution of Markowitz (1952) was to view this age-old activity in a scientifically rigorous manner, and bring three key elements to the forefront, namely, risk, return and correlations. Since the publication of Markowitz’ seminal paper, investment professionals have expensed significant resources in identifying, understanding and monetizing new sources of uncorrelated returns. This paper moves forward that narrative by focusing on Emerging Markets (EM) and demonstrating the effectiveness of earnings acceleration factors in building significantly better mean-variance optimized portfolios.